A Model For The Evaluation Of Leasing Proposals For Mining Investments - Nes?e Çelebi (Society for Mining, Metallurgy & Exploration, 1992)
It has never been easy to finance within mining sector. Leasing may be an alternative source of finance for mining investments. Leasing is acquiring the right of usage for an asset for a definite period of time without having the ownership of it. In this study, a model for analyzing the lease financing opportunities for mining investments under risk and suitable for establishing a satisfactory leasing policy for both lessee and lessor is developed. Using the model, it is possible to obtain an expected equilibrium lease amount acceptable by both lessor and lessee and also the expected range of the equilibrium lease amount as a decision tool. First the existing leasing policies are mentioned, then the developed model is described. A case study is presented to illustrate the use of the model in establishing a leasing policy. In conclusion, the usefulness of the model is discussed.